Kultúrák határán, metszéspontok a Bánságban: 896-1918 - Kókai, Sándor (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
The Bansag was a unique multicultural area in the historical Hungary, since then it mostly disappeared as the ethnical and linguistic rate changed. At the same time it is still a special cultural geographical region in the Carpatian-Basin. The Bansag’s cultural diversity is originated thanks to these nations: Romanians, Germans, Hungarians, Serbs, Croatians, Jewish, Bulgarians, Slovaks, Czechs, Gypsies, Turkish. The religious variety is also cha-racteristic because of the large number of religions (Orthodox, Catholicism, Protestant, Calvinist, Jewish and Muslim denomination). The Bansag was the model of peaceful coexistence between 1718 and 1918. Nowadays the maintenance of intercultural heritage is in danger. The region lost the multilingual character, which would mean connection with West-Europe.